2002
DOI: 10.23986/afsci.5729
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in Finnish soils in the 1900s with particular reference to the acid ammonium acetate soil test

Abstract: Comprehensive research into phosphorus (P) in soils and crops began in Finland in the early 1900s. The average amount of total P in the ploughed topsoil layer of mineral soils was about two tonnes per hectare in the 1930s, before the abundant use of fertilisers. The main chemical fractions of P in mineral soils were organic matter, primary apatite and secondary complexes of the hydrous oxides of Al and Fe. Of the smaller amounts of P in light peat soils, as much as 80% was present in stable organic compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…According to recalculation of the data published by Vuorinen and Mäkitie (1955), the P Ac values of mineral soils are closely correlated with the P values determined by the better-known Morgan's sodium acetate method from which the Finnish method was modified (Saarela 2002), (P Morgan = 0.694 * P Ac -0.27, n = 40, w = 1.5 -12, R 2 = 0.89). A very simple correction factor (0.7) can be used in comparing these methods in mineral soils.…”
Section: Soil and Plant Analysesmentioning
confidence: 83%
See 2 more Smart Citations
“…According to recalculation of the data published by Vuorinen and Mäkitie (1955), the P Ac values of mineral soils are closely correlated with the P values determined by the better-known Morgan's sodium acetate method from which the Finnish method was modified (Saarela 2002), (P Morgan = 0.694 * P Ac -0.27, n = 40, w = 1.5 -12, R 2 = 0.89). A very simple correction factor (0.7) can be used in comparing these methods in mineral soils.…”
Section: Soil and Plant Analysesmentioning
confidence: 83%
“…The amounts and chemical fractions of phosphorus (P) in Finnish soils were discussed in a recent review (Saarela 2002) and reported for 24 experimental sites (Saarela et al 2003). Native P reserves are fairly abundant in Finnish soils but occur mostly in stable inorganic and organic compounds which are poorly available to plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid ammonium acetate extraction, found to provide a good estimation of plant-available P in acidic Finnish soils (Saarela 2002), is also reported to be a suitable indicator for critical source areas of P load in pastures (Jansson and Tuhkanen 2003). Our results support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Also other nutrients, such as P and K, can be lost from the field either by leaching or in surface runoff (Ulén andMattsson 2003, Kayser et al 2007). The amounts of plant nutrients mineralised from mulched herbage are relatively small compared to those mobilised from previous applications of animal manure (Uusitalo et al 2007) and from the soil stock (Kaila 1967, Saarela 2002. Therefore, the residual effect of mulched herbage on subsequent ley growth may be minimal (cf.…”
Section: Impact Of Management On Ley Growthmentioning
confidence: 99%